Flood Risk Governance for More Resilience - Matczak, Piotr; Hegger, Dries (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Flood risks worldwide are being exacerbated due to urbanisation and the consequences of climate change. This poses a challenge to traditional managerial approaches to flood risk management that try to be 'fail-safe'. This book presents innovative and practical lessons on how to make flood risk management strategies 'safe-to-fail' and therewith more resilient. The book focuses on governance - rather than technical/managerial - approaches. As the book shows, new governance strategies are needed that ensure that flood risk management is not left to water managers alone. Various actors, including spatial planners, contingency agencies, NGOs and individual citizens, have a role to play in flood risk governance. Ten chapters assess different case studies from around the globe. These highlight the challenges and good practices related to learning, inter- and transdisciplinary cooperation, and debating and meeting the normative end-goals of flood risk governance. This book is essential reading for grounded scholars, reflexive policymakers and practitioners, and everyone else who is interested in contributing to more resilient and future-proof flood risk governance.